Kendala Normatif Penerapan E-Litigasi dalam Hukum Acara Mahkamah Konstitusi - Annisa Nurmalasari Hutapea; Eliza Yuniar; Kusuma Daniel Kusnadi; Sidi Ahyar Wiraguna (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The implementation of e-litigation in the Constitutional Court represents an institutional response to the demands of digital transformation within the constitutional justice system. However, its application faces fundamental normative challenges, particularly the lack of comprehensive regulations governing electronic proceedings and the insufficient protection of the constitutional rights of litigants in a digital environment. This study aims to analyze and identify normative gaps in the regulatory framework of e-litigation in the Constitutional Court and to examine their implications for safeguarding the constitutional rights of the parties involved. Employing normative legal research methods through statutory, conceptual and analytical approaches, this study finds that the existing regulations of the Constitutional Court on e-litigation remain inadequate in several key aspects. These include the legal validity of electronic evidence, data protection for litigants, guarantees of digital accessibility for marginalized groups and mechanisms for addressing technical disruptions that may affect court proceedings. The novelty of this research lies in the construction of a new normative framework, namely the Trias Digitalis Constitutionalis Principle, which encompasses three dimensions: equitable accessibility, digital procedural integrity and constitutional guarantees within the electronic sphere. This study recommends a comprehensive revision of the Constitutional Court’s regulations on e-litigation, along with the development of more detailed technical rules.